Active Sonar Waveform Design for High-range-velocity Resolution: A Review - Yaojun, Jia; Hongkai, Wei; Pingbo, Wang; Qiang, Chen (Recent Patents on Engineering, 2025)
Active sonar detects targets by transmitting acoustic signals and processing the echo, which is becoming the primary way of anti-submarine detection. From a large number of articles and patents, it can be seen that the design and processing of active sonar signals for high-range-velocity resolution has long been a problem of great interest. As a standard tool of waveform design, the ambiguity function (AF) based on a matched filter (MF) is always used to characterize the range-velocity resolution. In recent decades, a large number of scholars have studied various high-resolution waveforms with reverberation suppression performance and their improved versions. Although theoretically and technically, there is no ideal waveform that can be applied to all scenarios, we can select or design relatively optimal transmitted waveforms according to diverse tasks and purposes, performance indicators, and operating environments. In this patent paper, the high-resolution and anti-reverberation waveforms proposed in recent years are reviewed. Their advantages and disadvantages are evaluated comprehensively from the aspects of resolution, anti-reverberation, and detection performance, which provides guidance for waveform design and application. Compared with Comb spectrum (CS) and thumbtack signals, frequency modulation (FM) combination signal has a very broad development potential due to breaking away from the limitation of traditional MF processing.
Keywords: ambiguity function